Public perception towards river and water conservation practices: Opportunities for implementing urban stormwater management practices. (1st October 2018) - Gao, Yuling; Church, Sarah P.; Peel, Sara; Prokopy, Linda S.
Abstract: The effectiveness of urban stormwater management practices (SMPs) on local water quality is dependent on adoption rates reaching a critical mass. While numerous studies have measured the effectiveness of practices on controlling water quantity and improving water quality, few have focused on the perspective of the public. The purpose of this study was to identify individuals' perceptions of urban SMPs implementation in the public and private realms, and how longitudinal perceptions about the local river could inform future water resource management. Through the lens of environmental behavior theories, we performed statistical analyses on four surveys – 2006, 2009, 2014 and 2016 – administered to urban residents in the Wabash River watershed in Tippecanoe County, Indiana. Our findings show that residents' water quality awareness and sense of personal responsibility increase over the ten years studied. In particular, rain garden adopters have higher appreciation of the Wabash River and care about how the river functions than other SMP adopters and non-adopters. In terms of urban SMP adoption, results indicate that residents are supportive of integrating rain barrels and rain gardens into public spaces. Perceptions of SMP benefits related to functional benefits, rather than environmental benefits, are prevalent when considering implementing SMPs on personal property. In addition, respondents support reducing stormwater charges for adopters of such practices on private property. Although cognitive barriers exist in those who have yet to adopt the practices, including concerns about SMP effectiveness, maintenance, aesthetics, and risk of bugs and insects, adopters are less likely to perceive such barriers. This research suggests that making resources (i.e., skills, knowledge, equipment, funding) more accessible to the public is essential, but not sufficient to encourage pro-environmental behaviors. Promoting public involvement in watershed activities, increasing their awareness about how urban SMPs function, and emphasizing the functional benefits of practices can be effective in motivating adoption. Highlights: Public environmental awareness increased over the last decade studied. People value natural features of rain gardens and support public implementation. Reducing stormwater charges for adopters of practices can be an incentive. Emphasizing functionality of green practice helps motivate its adoption.